2019
DOI: 10.1021/acssuschemeng.9b00506
|View full text |Cite
|
Sign up to set email alerts
|

Does Nitrate Reductase Play a Role in Silver Nanoparticle Synthesis? Evidence for NADPH as the Sole Reducing Agent

Abstract: A leading hypothesis for silver nanoparticle biosynthesis suggests that the enzyme nitrate reductase plays a key role in the process, assisted by the coenzyme nicotinamide adenine dinucleotide phosphate (NADPH). Here, we show that NADPH alone can act as the reducing agent of silver nitrate salt to form silver nanoparticles. In fact, the addition of nitrate reductase during the synthesis causes a decrease in the reaction rate and broadening of the size distribution of the particles. The NADPH-synthesized partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(28 citation statements)
references
References 41 publications
2
24
0
2
Order By: Relevance
“…[ 202 ] Nevertheless, the role played by nitrate reductase in the reduction of Ag + has recently been challenged in experiments which demonstrates that NADPH may be used as the sole reducing agent for the synthesis of AgNPs (Figure 4D). [ 203 ]…”
Section: Microbes As Tiny Cell Factories For Biosynthesis Of Inorganimentioning
confidence: 99%
“…[ 202 ] Nevertheless, the role played by nitrate reductase in the reduction of Ag + has recently been challenged in experiments which demonstrates that NADPH may be used as the sole reducing agent for the synthesis of AgNPs (Figure 4D). [ 203 ]…”
Section: Microbes As Tiny Cell Factories For Biosynthesis Of Inorganimentioning
confidence: 99%
“…The results revealed that almost insignificant concentration level of protein (3.0 µg ml −1 ) was produced in the cell free filtrate as compared to the carbohydrate content, which was approximately 74.7 mg ml −1 . Generally, many different types of biomolecules are involved in the biosynthesis of metallic nanoparticles and among them one enzyme, known as NADPH-dependent nitrate reductase, is recognized to play a significant role as a reducing agent 25 . Therefore, it is suggested that A. fumigatus KIBGE-IB33 may also have metabolically synthesized this class of enzyme in very low concentrations which may have facilitated the reduction of AgNO 3 to elemental silver and then to silver nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…Several different fermentation factors, type of fungal strain used for production of fungal biomass and the components of the fermentation medium plays a major role in generating sufficient amounts of AgNPs. These factors are known to effect the characteristic properties of the silver nanoparticles at nanoscale range 25 . Some exopolysaccharides, produced by fungal strains, have been reported to be responsible for the reduction of AgNO 3 to silver ions and then to silver nanoparticles.…”
Section: Resultsmentioning
confidence: 99%
“…In recent work, Hietzschold et al (2019) showed that nanoparticle synthesis occurred by the action of NADPH, without any need for the nitrate reductase enzyme. This is particularly interesting, since it leads to the possibility of using different organisms for the synthesis of nanoparticles, without the necessary condition of reductase enzyme production.…”
Section: Synthesis Mechanismsmentioning
confidence: 99%